Teaching percussion : with DVD - Cook, Gary, 1951- (Belmont, CA : Thomson Schirmer, 2006)
From the publisher. Become a better music teacher with Teaching Percussion with accompanying 2-DVD set! Providing a comprehensive introduction to every aspect of percussion education, technique, and performance, this music text guides you towards a greater musical awareness and improved technique. Illustrations, examples, and exercises acquaint you with the special needs of all percussion instruments. You will gain a greater insight into music learning and performance through the inclusion of up-to-date techniques and numerous exercises.
General considerations and prerequisites -- Basic percussion technique through the study of the snare drum -- Multiple percussion -- Keyboard percussion -- Timpani -- Bass drum, cymbals, and accessories -- Percussion instruments of the world -- Drum set -- Marching percussion -- Musical interpretation of percussion parts -- Supplemental playing exercises -- Future trends in percussion education -- Orchestral excerpts for percussion and discography of percussion music -- Select percussion solo and ensemble music.
Discography: pages 474-482.
Includes bibliographical references and index.
Keywords: Percussion instruments -- Instruction and study; Percussion instruments -- Instruction and study